Hemocompatibility of hyaluronan enhanced linear low density polyethylene for blood contacting applications. Issue 5 (30th September 2017) - Simon‐Walker, Rachael; Cavicchia, John; Prawel, David A.; Dasi, Lakshmi Prasad; James, Susan P.; Popat, Ketul C.
Abstract: Despite their overall success, different blood‐contacting medical devices such as heart valves, stents, and so forth, are still plagued with hemocompatibility issues which often result in the need for subsequent replacement and/or life‐long anticoagulation therapy. Consequently, there is a significant interest in developing biomaterials that can address these issues. Polymeric‐based materials have been proposed for use in many applications due to their ability to be finely tuned through manufacturing and surface modification to enhance hemocompatibility. In this study, we have developed a novel, hydrophilic biomaterial comprised of an interpenetrating polymer network (IPN) of hyaluronan (HA) and linear low density polyethylene (LLDPE). HA is a highly lubricous, anionic polysaccharide ubiquitously found in the human body. It is currently being investigated for a vast array of biomedical applications including cardiovascular therapies such as hydrogel‐based regenerative cell therapies for myocardial infarction, HA‐coated stents, and surface modifications of polyurethane and metals for use in blood‐contacting implants. The aim of this study was to assess the in vitro thrombogenic response of the hydrophilic polymer surface, HA‐LLDPE for future potential use as flexible heart valve leaflets. The results indicate that HA‐LLDPE is non‐toxic and reduces thromobogenicity as compared to LLDPE surfaces, asserting its feasibility for use as a blood‐contacting biomaterial. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 106B: 1964–1975, 2018.